Corporate governance, dynamic capabilities and business performance in companies listed in Brasil, Bolsa, Balcão S/A (B3 S/A) - Barbosa, Flávia Lorenne Sampaio; Cabral, Jose Ednilson de Oliveira; Nascimento, João Carlos Hipólito Bernardes do; Bizzaria, Fabiana Pinto de Almeida (Revista de Administração da UFSM, 2021)
Purpose- The main objective is to analyze the direct effect of Corporate Governance (CG) on Dynamic Capabilities (DCs) and on Business Performance (BP), and the moderating and/or mediating impact of DCs on the CG-BP relationship. Methodology- The quantitative analysis was performed through PLS-SEM. Data were collected through a survey involving companies listed in B3 S/A from 2014 to 2016, except for companies from the financial sector. The final sample encompassed 195 companies per assessed year, thus totaling 585 observations concerning 2014, 2015 and 2016. Findings- Confirmed the direct and positive effect of CG on DC development, as well as DC’s influence on BP and the mediating effect of DC on the CG - BP relationship. The main conclusion was that DCs are a powerful mediating influence on the CG-BP relationship. Hence, even with efficient corporate governance mechanisms, the companies must make decisions in line with their dynamic capabilities as a way to reach better business performance. Limitations- Research cross-section method of data collection; and universe of companies listed in the Brazilian stock market. Practical implications- For example, the rejected hypothesis about the direct effect of CG on BP and the confirmation of the indirect effect via DCs suggests the analysis of aspects related to costs with monitoring procedures applied to agency conflicts and to complementary factors that must be achieved in order to boost performance. On practical terms, the results contribute to companies that look for the best and most satisfactory performance in the markets they work in.